UMPSA Vice-Chancellor supports students sitting for final examinations - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 3 February 2025 – The Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dr. Yatimah Alias, today reached out to UMPSA students by distributing bottled water and bread to them before they sat for their Semester I Academic Session 2024/2025 final examination, held at the UMPSA Multipurpose Hall, Pekan.